Performance of selective and differential media in the primary isolation of yeasts from different biological samples - Silva, Jaqueline Otero; Franceschini, Silvio Antônio; Lavrador, Marco Aurélio Sicchiroli; Candido, Regina Célia (Springer Nature, 2004)
In view of the increase in yeast infections, especially polymicrobial ones, differential culture media have acquired increasing importance. The present study evaluated the Sabouraud chloramphenicol, Biggy agar, Pagano Levin agar and CHROMagar Candida media in terms of isolation, number of yeast colony forming units per plate, and inhibition of bacteria and filamentous fungi. To this end, we used 223 biological samples, including feces, and oral, vaginal and anal mucosae from 86 patients presenting or not symptoms of fungal infections. The four media did not differ significantly in terms of detection of yeast-positive cultures. The number of colony forming units per plate ranged from zero to 2.380, with a predominance of counts of 1 to 9 colonies per plate. No significant differences were observed among the four culture media in terms of number of colonies counted, for each kind of biological material. Fifteen species belonging to the genera Candida, Saccharomyces, Cryptococcus, Trichosporon and Rhodotorula were isolated, with C. albicans being the predominant species, followed by C. parapsilosis and R. rubra. CHROMagar Candida and Biggy agar were complementary in the isolation of the different species and favored a greater recovery of polymicrobial cultures. Pagano Levin agar isolated the smallest variety of species. Sabouraud chloramphenicol agar was the least effective in terms of bacterial inhibition and favored a greater development of filamentous fungi. The results suggest that more than one culture medium should be used for an adequate primary isolation.
Keywords: Biggy agar; Candida; CHROMagar Candida; Culture media; Pagano Levin agar; Yeasts